Next steps for assessing ocean iron fertilization for marine carbon dioxide removal - Buesseler, Ken O.; Bianchi, Daniele; Chai, Fei; Cullen, Jay T.; Estapa, Margaret; Hawco, Nicholas; John, Seth; McGillicuddy, Dennis J.; Morris, Paul J.; Nawaz, Sara; Nishioka, Jun; Pham, Anh; et al. (Frontiers in Climate, 2024)
There are many potential approaches to marine carbon dioxide removal (mCDR), of which ocean iron fertilization (OIF) has the longest history of study. However, OIF studies to date were not primarily designed to quantify the durability of carbon (C) storage, nor how wise OIF might be as an mCDR approach. To quantify C sequestration, we introduce a metric called the “centennial tonne,” defined as 1,000 kg of C isolated from atmospheric contact for on average at least 100 years. We present the activities needed to assess OIF from a scientific and technological perspective, and additionally, how it might be responsibly studied and potentially deployed. The five activities include: field studies in the Northeast Pacific; improved modeling for field studies, data assimilation and predictions at larger scales; improvements in monitoring, reporting and verification (MRV) for C, and also MRV for tracking ecological and environmental impacts; and developing new iron sources and their delivery, to increase efficiencies and reduce costs. The fifth activity is to understand whether public and community support exists for OIF, and what governance structures might support further research and possible deployment of OIF. This article is written by a multidisciplinary experts group called Exploring Ocean Iron Solutions (ExOIS) that is organized around a responsible code of conduct. Of the mCDR approaches, OIF has the potential to be low cost, scalable, and rapidly deployable. Reducing CO2 emissions must lead the way, but there is also an urgency to decide under what conditions and whether OIF might be deployed or not.